ANALYSING THE EFFECT OF RETURN ON EQUITY, RETURN ON ASSETS AND EARNINGS PER SHARE TOWARD SHARE PRICE: AN EMPERICAL STUDY OF FOOD AND BEVERAGE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Tamuntuan, Ursula (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT   Simplicity of using financial ratios offers the investors an easy way to comprehend and predict a company’s financial performance. The objective of this research is to identify the effect of some financial ratios, which are Return on Equity (ROE), Return on Assets (ROA) and Earnings per Share (EPS), toward share price of Food and Beverage companies listed on Indonesia Stock Exchange (IDX). Twelve companies’ financial report from 2010 to 2014 are collected by using purposive sampling method. Tests conducted show that ROE, ROA and EPS simultaneously have significant effect toward the share price, yet partially, only EPS does significantly affect the share price; both ROE and ROA do not have significant effect to the share price. Therefore, for those who are interested in investing on the food and beverage companies listed on IDX should put Earning per Share as the top indicator for their investment decision process.   Keywords: Return On Equity, Return On Assets, Earnings Per Share, Share Price